Paradigma Epistemologi Filsafat Pendidikan Islam sebagai Landasan Pembelajaran di SMP IT At-Taqwa Grabag Magelang - Khidir Mansyur; Mujiburrohman Mujiburrohman (TSAQOFAH, 2026)
The epistemological paradigm in Islamic educational philosophy has a fundamental role in building a conceptual foundation for learning that integrates revelation, reason, and empirical experience as sources of knowledge. The challenges of contemporary education require a learning model that is oriented not only toward mastery of knowledge but also toward the formation of students’ character and spiritual values. This study aims to analyze the epistemological paradigm of Islamic educational philosophy as a foundation for learning at SMP IT At-Taqwa Grabag Magelang. This study employed a qualitative approach with a case study design. Data were obtained through in-depth interviews, participatory observation, and documentation studies. The data were analyzed through data reduction, data display, and conclusion drawing, while data validity was strengthened through source and technique triangulation. The results show that the epistemological paradigm of Islamic education at SMP IT At-Taqwa Grabag Magelang was built through the integration of revelation, reason, and experience as sources of knowledge. The implementation of this paradigm is reflected in lesson planning, the implementation of the teaching and learning process, the habituation of Islamic values, and evaluation that emphasizes the balance of cognitive, affective, and psychomotor aspects. This paradigm contributes to strengthening students’ religious character, critical thinking skills, and moral awareness. The conclusion of this study emphasizes that the epistemology of Islamic educational philosophy serves as an important foundation for building a holistic learning system oriented toward the integral development of human potential. The implications of the study include theoretical contributions to the development of Islamic educational philosophy studies and practical implications for Islamic educational institutions in designing learning based on values, knowledge, and character.